The effect of periodization on training program adherence (2021)
The present research aimed to study the effect of three different training periodization (traditional, reverse, and free training) on the aerobic performance, motivation, and adherence of physically active athletes. We analysed the adherence to three different periodization training programs: traditional, reverse, and free training periodization on the adherence of amateur triathletes. For this aim, the individual adherence, motivation, and aerobic performance time and heart rate (in a 1000 m running test) were evaluated before and after the completion of the three different 8-week periodization programs. The level of adherence to the reverse periodization was significantly higher than in traditional and free training. The number of dropouts in reverse and traditional periodization was similar but lower than in the free training. Finally, neither of the periodization programs improved aerobic performance and reverse training periodization decreased heart rate of participants in a 1000 m running test.